Postoperative opioid-free analgesia in dogs undergoing tibial plateau leveling osteotomy: a feasibility study - Didier, Caroline; Faucher, Sarah; Sarra Ferrer, Marti; Lapouge, Mathilde; Junot, Stéphane; Jourdan, Géraldine (Frontiers in Veterinary Science, 2024)
Objectives This study was designed to prospectively evaluate the feasibility of an opioid-free anesthesia protocol and describe the quality of recovery and management of postoperative analgesia in dogs after a tibial plateau leveling osteotomy (TPLO). Methods In total, 20 dogs presented for TPLO were included. After premedication with intravenous (IV) medetomidine (0.005–0.007 mg/kg) and midazolam (0.2 mg/kg), the dogs were anesthetized using ketamine (2 mg/kg) and propofol and maintained with isoflurane and ketamine CRI (0.6 mg/kg/h). Sciatic and femoral nerve blocks were performed with bupivacaine 0.5% (0.087 +/− 0.01 and 0.09 +/− 0.02 mL/kg, respectively). Meloxicam (0.2 mg/kg IV) was administered intraoperatively, after osteotomy. Fentanyl (0.002 mg/kg IV) was administered intraoperatively, as rescue analgesia in the case of sustained increase in cardiorespiratory variables. Two pain scores (French 4A-VET and Glasgow short form) were performed at conscious sternal recumbency and 2, 4, 6, 8, 12, and 20 h after extubation and compared to baseline using a Friedman test followed by a Nemenyi post-hoc test. The time taken for the first food intake and urination was reported. Results Intraoperative opioid-free anesthesia was feasible in 11 dogs, whereas 9 dogs received fentanyl once during arthrotomy. No opioid postoperative rescue analgesia was required. Food intake occurred within 6 h, and all dogs were discharged after 24 h without any complication. Conclusion Total opioid-free postoperative analgesia was achieved in all dogs, with adequate recoveries. Although opioid-free anesthesia was feasible in 55% of the population, a single dose of fentanyl was necessary in 45% of the dogs during arthrotomy.